1997
DOI: 10.1046/j.1469-8137.1997.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Can an increased copper requirement in copper‐tolerant Mimulus guttatus explain the cost of tolerance?

Abstract: SUMMARYIf metal tolerant plants, by virtue of their tolerance mechanism, are less efficient at the uptake, distribution or utilization of metals then essential micronutrient deficiency may occur at the low levels of metal supply found on non-mine soils. This argument forms the basis of the metal requirement hypothesis put forward to explain the lower fitness of tolerant individuals on uncontaminated soil, the so called 'cost of tolerance'. In this paper, copper balance was investigated in Mimulus guttatus Fisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 36 publications
1
26
1
Order By: Relevance
“…On the contrary, copper tolerant and non-tolerant genotypes of Mimulus guttatus were similarly affected by decreasing copper supply, which is against the cost of living in the presence of copper excess. Mechanisms underlying a higher requirement of copper in cuprophytes need further study (Harper et al 1997(Harper et al , 1998. In Zn hyperaccumulators, the higher Zn requirement is proposed to be related to efficient sequestration mechanisms and deregulated Zn deficiency response (reviewed in Verbruggen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, copper tolerant and non-tolerant genotypes of Mimulus guttatus were similarly affected by decreasing copper supply, which is against the cost of living in the presence of copper excess. Mechanisms underlying a higher requirement of copper in cuprophytes need further study (Harper et al 1997(Harper et al , 1998. In Zn hyperaccumulators, the higher Zn requirement is proposed to be related to efficient sequestration mechanisms and deregulated Zn deficiency response (reviewed in Verbruggen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A detoxification mechanism might use energy and other resources that are then unavailable for other fitness traits such as growth and reproduction (Sibly and Calow 1989). Alternatively, resistant individuals might be less efficient at metal uptake, thus leading to micronutrient deficiency in unpolluted environments (Harper et al 1997). Field and laboratory studies suggest that metal tolerant plants have a selective disadvantage in low metal environments; however, it is possible that plants adapted to mine environments are also resistant to other mine stressors, such as low nutrient levels and increased susceptibility to drought (Harper et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, resistant individuals might be less efficient at metal uptake, thus leading to micronutrient deficiency in unpolluted environments (Harper et al 1997). Field and laboratory studies suggest that metal tolerant plants have a selective disadvantage in low metal environments; however, it is possible that plants adapted to mine environments are also resistant to other mine stressors, such as low nutrient levels and increased susceptibility to drought (Harper et al 1997). Evidence for evolution and fitness costs of metal tolerance in invertebrates is not as evident as in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although pollution tolerant plants may have a selective advantage in contaminated soils, they are often much smaller in size, produce fewer seeds (often of poorer quality), have a lower biomass production and have lower flowering potential compared with conspecifics from uncontaminated soils when both are grown in uncontaminated soil (Pollard 1980;Wilson 1988;Wu 1990;Harper et al 1997;Stanton et al 2000). It has also been shown that metal-tolerant plants in some instances can be inferior to intolerant plants when grown on uncontaminated ("normal") soil (Cook et al 1971;Hickey and McNeilly 1975).…”
Section: Introductionmentioning
confidence: 99%